Implementasi Kombinasi Metode AFF dan FBET Untuk Peningkatan Kualitas Citra - Pahala Sirait; Irpan Adiputra Pardosi; Apriyanto Halim; Tommy - (Jurnal SIFO Mikroskil, 2019)
Image enhancement is one of the most popular research topics currently in the field of image processing. Often image has poor quality caused by various factors such as lighting factor, enviromental factor or low quality of camera, and others. A number of these disturbances often become a barrier in improving the image quality where handling is the main objective of this research is done in the form of methodology base on the combination of AFF dan FBET algorithm. The result of the test on the proposed methodology show that in the process of noise loss continued with the image sharpening process obtained the value of PSNR = 18.56 dB is more optimal than the first done image sharpening process with the value of PSNR = 18.10 dB.